The Last Kids on Earth - Book 1 - Brallier, Max; Churilla, Brian; Peterson, Scott, 1968-; Alpi, Victor; Duarte, Gonzalo (Colorist) (New York, New York : Viking, an imprint of Penguin Random House LLC, 2024)
"Ever since the monster apocalypse hit town, average thirteen-year-old Jack Sullivan has been living in his tree house, which he's armed to the teeth with catapults and a moat, not to mention video games and an endless supply of Oreos and Mountain Dew scavenged from abandoned stores. But Jack alone is no match for the hordes of Zombies and Winged Wretches and Vine Thingies, and especially not for the eerily intelligent monster known only as Blarg. So Jack builds a team..."--
Keywords: Survival -- Comic books, strips, etc; Friendship -- Comic books, strips, etc; Monsters -- Comic books, strips, etc; Zombies -- Comic books, strips, etc; Tree houses -- Comic books, strips, etc; Comic books, strips, etc. -- United States; Survival -- Fiction; Friendship -- Fiction; Monsters -- Fiction; Zombies -- Fiction; Tree houses -- Fiction; Cartoons and comics; Apocalyptic comics; Action and adventure comics; Comics (Graphic works); Graphic novels